(untitled) (Práxis Educativa, 2024)
The study of the gender gap and strategies for the elimination of inequalities in science and technology is a complex line of research that analyzes multiple dimensions, focusing on those that have greater explanatory power such as gender stereotypes, the dynamics and processes that allow overcoming them, socialization and social construction of science, and the need to design innovative theoretical and empirical studies that respond to these problems. Thus, this article is based on qualitative research, and the way to carry it out was through a bibliographic and documentary review with the aim of showing the barriers and glass ceilings of women in science, as well as the most significant data on their promotion, presence and scientific career in Spain. It was concluded that the observed transformations may mean several things. On the one hand, it is possible that we are witnessing a weakening of some gender stereotypes when it comes to choosing a professional career, although, on the other hand, these transformations are not sufficient to undertake the structural, institutional, or social and cultural context reforms that are necessary for the promotion, leadership and visibility of women, both in scientific careers and within institutions. Keywords: Science and women. University. Gender gap.